The Misreading as a Tactic or the Tactic of Misreading: reflections on João Gilberto, Dorival Caymmi and the pursuit of legitimacy of an artistic identity (Orfeu, 2016)
In this article, of a musicology nature, we’ll make a comparative analysis using two interpretations of the music Rosa Morena: the first one by his own composer, Dorival Caymmi (1914-2008), and the other one by João Gilberto (1931- ). From the use of the concept of Field, defined by Bordieu (1996;2013), we’ll approach the scenery in which the album “Chega de Saudade” is released.Our premise is that Gilberto, when using the song “Rosa Morena” as a base for his specific artistic procedures, establishes a misreading of the Caymmi’s work. Identified as a deforming action, the misreading would be a tool of a tactical nature, acting inside an environment of intense conflicts and responsible for capitalize symbolic assets for Bossa Nova, however, such an economy will happen in a double way: in the same time the specificities of the new style becomes stronger, the misreading makes it weaker, due to the conection stablished by the popular music tradition that Caymmi represents.
Keywords: João Gilberto; Dorival Caymmi; Identity; Misreading; Symbolic Tactic